Effectiveness of Using the Mobile Disaster Exercise Application on the Level of Disaster Response Knowledge Among Nursing Students - Nur Rahmawati, Ika; Sunarto, Sunarto; Harnanto, Addi Mardi; Sudiro, Sudiro (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Disasters can occur anywhere and happen to anyone who can cause loss of life, psychological impacts, material loss and environmental damage. Everyone is expected to know the attitude they should take when a disaster occurs, including the role of nursing students. One way to increase disaster response knowledge is by using the Mobile Disaster Exercise Application. This research aims to describe the effectiveness of using the Mobile Disaster Exercise Application on disaster response knowledge of Among Nursing students. Methods: This research is a quantitative research with a quasi-experiment type with a pretest-posttest with control group design. The sample for this research was 60 nursing students from the Surakarta Ministry of Health Polytechnic in the experimental group in the form of the Mobile Disaster Exercise Application and 58 people in the control group in the form of online lectures, then the data was processed using a paired sample t-tes. Results: Health education through the Mobile Disaster Exercise Application media was effective in increasing disaster response knowledge among nursing students, obtained a mean of 19.83 with a value of p=0.000 (p<0.05). Meanwhile, in the control group in the form of online lectures, a mean of 16.59 was obtained with a value of p=0.000 (p<0.05). Conclusion: The Mobile Disaster Exercise application is effective in increasing disaster response knowledge among Nursing Students.